Sum-Difference Method in Monopulse Radar: A Review - Alam, Alam; Tahcfulloh, Syahfrizal (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2024)
This article reviews the sum and difference methods on monopulse radar used to detect targets during the tracking process. These methods are described in detail and comprehensively regarding optimizing the size of the subarray elements, optimizing the radiation energy of tracking targets, optimizing for obtaining lower sidelobe level and optimizing computations for digital processing. Considerations of potential strategies for configuring an implementable monopulse radar are also given. This article also provides answers when faced with the challenge of building a monopulse subarray radar that meets the implementation needs of both software and hardware. The expected result of this subarray on monopulse radar is to obtain flexible and general capabilities for detection and tracking that can adapt to target and environmental conditions, including countering interference and jamming.